Assessing the developing knowledge-base of product counterfeiting: a content analysis of four decades of research - Sullivan, Brandon A. (Trends in organized crime, 2017)
Considering the steady and rapid growth of product counterfeiting and the damage it causes to society, it is important for criminology and criminal justice scholars to assist criminal justice officials, industry practitioners, and law makers in understanding the product counterfeiting problem and developing strategies to combat it. However, for researchers to be effective in their advisory role they must first establish what is known about product counterfeiting. As a first step in this process, we investigated relevant published research through a content analysis of 47 articles discussing product counterfeiting published in criminal justice and criminology journals through 2014. We analyzed various characteristics about the articles themselves, their authors, the journals they appeared in, and the nature and extent of their focus on product counterfeiting. We conclude this study with an evaluation of the state of product counterfeiting research and recommendations for future research.